2019
DOI: 10.1111/bjh.15821
|View full text |Cite
|
Sign up to set email alerts
|

How we manage haemostasis during sepsis

Abstract: Summary Sepsis may be associated with activation of the coagulation system and, in its most severe form, may result in disseminated intravascular coagulation (DIC). Initially, there is thrombosis primarily affecting small and medium sized vessels and contributing to organ dysfunction, but continued activation results in consumption of coagulation factors. This results in prolongation of global coagulation parameters. Often thrombocytopenia is the initial feature in sepsis, which may be followed by prolongation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Thus, identifying patients earlier in the course of their hemostatic dysfunction would be important for potential management, especially in the intensive care unit. 17 Coagulopathy in patients with sepsis continues from an initial compensatory phase to the decompensated stage of DIC. Although there is still debate regarding the definition of coagulopathy, it is generally suggested as "a condition in which the ability of the blood to clot is impaired," 18 and conventionally, the term coagulopathy predominantly had represented a hemorrhagic state.…”
Section: Pathophysiology Of Sepsis-induced Coagulopathy and Dicmentioning
confidence: 99%
“…Thus, identifying patients earlier in the course of their hemostatic dysfunction would be important for potential management, especially in the intensive care unit. 17 Coagulopathy in patients with sepsis continues from an initial compensatory phase to the decompensated stage of DIC. Although there is still debate regarding the definition of coagulopathy, it is generally suggested as "a condition in which the ability of the blood to clot is impaired," 18 and conventionally, the term coagulopathy predominantly had represented a hemorrhagic state.…”
Section: Pathophysiology Of Sepsis-induced Coagulopathy and Dicmentioning
confidence: 99%
“…Coagulation plays a defensive role during infections by limiting the dissemination of pathogens and contributing to their destruction. 10 The systemic inflammatory response during sepsis includes the increased expression of procoagulant cytokines such as interleukin-1 (IL-1), IL-6, and tumor necrosis factor-α, 11 which also activate platelets. 12 Locally, bacteria and viruses elicit a prothrombotic environment both indirectly, through endothelial damage and inflammation, 13 and directly, by inducing the expression of tissue factor on monocytes and endothelial cells, 14 activating the intrinsic coagulation pathway, 10 inhibiting the physiologic anticoagulation mechanisms, 15 and promoting platelet aggregation, 16 particularly via complement activation.…”
Section: Pathophysiologymentioning
confidence: 99%
“…For sepsis patients, anticoagulation therapy should be administered in cases of persistent decline in platelet count, persistent elongation of coagulation time, organ dysfunction due to microthrombosis, and when required to manage thrombotic events duringthe hypercoagulable stage of DIC [107]. If the patient is in a hypocoagulable state and at risk for bleeding, anticoagulation therapy may be providedwhile replenishing the patient's coagulation substrates [108]. Randomized controlled trials (RCTs) have shown that recombinant activated protein C, tissue factor pathway inhibitor (TFPI), and thrombomodulin (TM) have no effect in improving the prognosis of sepsis [109][110][111].…”
Section: Medical Treatmentmentioning
confidence: 99%